Shared decision-making in post-coercion debriefing interventions in psychiatry – a scoping review - Froelich, Katharina; Schürmann, Jan; Huber, Christian G.; Trachsel, Manuel (Frontiers in Psychiatry, 2024)
Debriefing is recommended after any coercive measure in psychiatry, but there are no wellestablished standards, and its effectiveness remains unclear. Incorporating shared decision-making (SDM) into post-coercion debriefing interventions has potentially beneficial effects. This scoping review provides an overview of the general characteristics of such interventions and the extent to which SDM elements are already used in such interventions. A total of 2562 references were identified in the scholarly databases Embase, PubMed, Web of Science, and PsycINFO. In addition, 14 articles were identified through manual searches of reference lists. 42 full-text articles were screened for eligibility, 13 articles met the eligibility criteria and were further analyzed. No intervention tool was found that clearly included all SDM elements. However, three elements of SDM were present at least partially in all interventions: definition and explanation of the health care problem, the clarification of the patient's values and preferences, and a decision or explicit deferral of the decision. Further research is needed to systematically examine the implementation and clinical effectiveness of post-coercion debriefing interventions, particularly regarding the inclusion of shared decision-making elements.